Design and fabrication of a holey fiber microfluidic device with transverse micro-channel - Shum, Perry Ping (2014)
In this report, we present a design of holey fiber structure with six air holes in the cladding and a transverse microfluidic channel intersecting the silica core for liquid detection purpose. The simulation results suggest an improved refractive index sensitivity of the proposed structure compared to that of a single mode fiber with similar transverse channel. The proposed holey fiber structures are fabricated and characterized.